Pemanfaatan Media Smart TV Berbasis Ramah Anak dalam Meningkatkan Perkembangan Kognitif dan Bahasa Anak Usia 2 Tahun - Yuniatari; Ria Astuti (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
The rapid development of the era and technological advances make it easier for someone to compile and present information, including in the teaching and learning process. Teaching and learning activities require media so that learning objectives are achieved. One of the media innovations that utilizes sophisticated technology is smart television (smart TV). This study aims to describe the use of child-friendly smart TV media in improving the cognitive and language development of 2-year-old children. The study uses a descriptive qualitative type. The subjects of the study were two 2-year-old children, managers, and teachers at Husna Day Care Pamekasan. Data collection techniques used observation, interviews, and documentation. Data analysis techniques used the Miles and Huberman model in the form of steps, namely: 1) data collection, 2) data reduction, 3) data presentation, and 4) drawing conclusions. The results of the study showed that the use of child-friendly smart TV learning media at Husna Day Care Pamekasan was proven to be able to improve the cognitive and language development of 2-year-old children.